A review on mobile device's digital forensic process models - Farjamfar, Anahita; Abdullah @ Selimun, Mohd Taufik; Mahmod, Ramlan; Udzir, Nur Izura (Maxwell Science Publication, 2014)
The main purpose of this study is to discuss the different comparative studies on digital forensics process models specially in the field of mobile devices. In order to legally pursue digital criminals, investigation should be conducted in a forensically sound manner so that the acquired evidence would be accepted in the court of law. Digital forensic process models define the important steps that should be followed to assure the investigation is performed successfully. There are a number of digital forensic process models developed by various organizations worldwide, but yet, there is no agreement among forensics investigation and legislative delegation which procedures to adhere to; specially in the case of facing mobile devices with latest technologies. This is vital, as mobile phones and other mobile devices such as PDAs or tablets are becoming ever-present as the main technology platform around the world and people are obtaining and using mobile phones more than ever. In this study we will give a review of the proposed digital forensics process models within last 7 years and to discuss the need for a consensus to follow the same underlying approaches while continually updating digital forensics process models to cover new emerging technologies and devices.